Baricitinib as monotherapy for treatment of rheumatoid arthritis: analysis of real-world data - Edwards, Christoper J.; Takeuchi, Tsutomu; Finckh, Axel; Kleyer, Arnd; Haladyj, Ewa; Gerwien, Jens Gammeltoft; Treuer, Tamás; Zaremba-Pechmann, Liliana; Smolen, Josef S. (Current Medical Research and Opinion, 2024)
Objective: Baricitinib is an oral, reversible and selective inhibitor of Janus kinase (JAK)1 and JAK2 that is approved as monotherapy or in combination with methotrexate for the treatment of adults with moderate-to-severe active rheumatoid arthritis (RA) who have responded inadequately to disease-modifying antirheumatic drugs. Evidence supporting the approved monotherapy indication is growing in real-world settings that reflect routine clinical practice. Methods: Results of separate analyses of real-world data from the observational prospective RA-BE-REAL, Erlangen Baricitinib cohort, the BSRBR-RA, and Swiss Clinical Quality Management in Rheumatic Diseases (SCQM) registries, and the retrospective ORBIT-RA and SUSTAIN long-term chart reviews were reported, documenting baseline data and outcomes for a total of 932 patients with active RA receiving baricitinib as monotherapy. Findings were contrasted with those from a total of 850 patients receiving the drug as combination therapy. All analyses were descriptive and completed in September 2022. Results: Across the patient registries and observational studies, 39.4%–69.6% of patients received baricitinib monotherapy for the treatment of active RA. In these patients, after about 6–12 months of treatment, 40.7%–93.8% and 55.6%–88.0% achieved remission or low disease activity according to the composite measures of disease activity 28-joint count and Clinical Disease Activity Index, respectively. Treatment continuation/discontinuation rates differed across the studies. Conclusion: These findings suggest that baricitinib monotherapy can be a suitable treatment option in routine clinical practice for patients with RA, when used in accordance with current guidelines.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Arthritis; biological therapy; registries; rheumatoid